Penerapan Model Pembelajaran Probing Prompting dalam Upaya Meningkatkan Hasil Belajar Siswa pada Tema Udara Bersih Bagi Kesehatan di Kelas V.A SD Negeri 114/X Pandan Jaya - Deby Utoyo (Departement of Mathematics Education, 2021)
This study aims to disclose information and discuss the application of the Probing Prompting Learning Model in an Effort to Improve Student Learning Outcomes on the Theme of Clean Air for Health in Class V.A SD Negeri 114/X Pandan Jaya. This research is included in the type of classroom action research (CAR). This research was carried out in this research was carried out at SD Negeri 114/X Pandan Jaya. The time of this research was carried out in the odd semester of the 2021 - 2022 school year, which began in August 2021. The subjects in this study were 25 class V.A students. The research procedure consisted of two cycles with four stages of research starting from planning, implementing, observing and reflecting. Data collection in this study was carried out using observation sheets, field notes, learning outcomes test sheets, and documents. The data were analyzed using the percentage formula. The results of this study indicate that the Probing Prompting Learning Model on the Theme of Clean Air for Health can improve student learning outcomes in class VA SD Negeri 114/X Pandan Jaya which is marked by an increase from pre-cycle (20%), cycle I (60%), cycle II (92%).